(3JHUjQ GdefJHg HJMQjQ GdeTJHgs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s ((3YHO GdQMef Hf eMeO GdSfOjSi s)
(3ChdgG (B:s
(3bGd GdYdGeI GdYSbdGfi GdMeO ddg LGeY GdfGS djhe dGQjH ajg CeG HYO aGffi deG YdbJ cJGH GdeTJHg GdPi dNUg GdMGaX GdTgjQ GHh YHO Gddg GdPgHi QMeg Gddg s
(3BNQgG (B:s
(3hdGjSJZfi WGdH GdMOjK Yf VHW eG jQO ef Pdc ef GdCSeGA , hdh de jcf dge QhGjI BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3HChdg agQS cJHg bGSe Hf bfOjd GdTbjQi Sfg (B836s
(3ajg VHW s
(3Ydjg JedcGJ s
(3Hg GdJYbjHI s
(3fbdJ GdfSNI Yf fSNI HNW GdYdGeI HQgGf GdOjf Hf NVQ s
Keywords: (3GdJGQjNs